Aberrant Development of Enteric Glial Cells in the Colon of Hirschsprung's Disease - Zhou, Tingting; Liu, Wei; Yu, Xiaofang; Cao, Zengcai; Mu, Weijing; Hou, Peimin; Ren, Chuantao; Li, Aiwu (Frontiers in Pediatrics, 2021)
Abstract Objective: The aim of this study was to explore the development of enteric glial cells (EGCs) in different segments of Hirschsprung's disease (HSCR). Methods: Colonic specimens from 35 children with HSCR were selected to analyze the relative expression of glial fibrillary acidic protein and S100 calcium-binding protein B using western blotting and real-time fluorescence quantitative PCR. Immunofluorescence and immunohistochemical staining were performed to determine the distribution of myenteric EGCs and neuronal cells in different segments of HSCR. Results: There was a trend of diminished protein and mRNA expression of glial fibrillary acidic protein and S100 calcium-binding protein B from the proximal, dilated, and transitional segments to the aganglionic segment (P<0.05). Immunofluorescence and immunohistochemistry showed that the EGCs in the aganglionic, transitional and dilated colonic muscles were morphologically abnormal, which was consistent with the dysplasia of myenteric neurons. Conclusion: Aberrant development of myenteric EGCs was observed in the colon of HSCR, which may affect the survival of enteric neurons.